VISI PENDIDIKAN PERSPEKTIF ISLAM, FILOSOFI, PSIKOLOGI DAN SOSIOLOGI - Muhsin Muhsin; Ahmad Muadin (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2023)
Educational institutions have recently experienced a period of growth which is full of competition, especially the Islamic-based education level which must be fully innovative and better, always updating the right information, making breakthroughs full of strategic innovation and mobilizing skills and commitment among all madrasahs. In fulfilling its mission as an educational level, MI/MTS/MA should be managed as well as possible so as to achieve the vision and mission that has been set. The purpose of this study is to describe the vision of education from the perspective of Islam, psychology, philosophy and sociology. In this study, the vision of education can be seen from several perspectives that are able to interpret the humanistic vision of education, that is, to humanize humans because recently there has been a lot of education that is still wrong in understanding and implementing the vision of education. The research method used is a qualitative approach with descriptive analysis methods based on literature searches or literature searches. Literature review is an activity related to collecting data on library materials, reading and storing research materials, and analyzing them. The results of the study show that insight into the vision of education based on religion, philosophy, psychology and sociology is the eternal essence of efforts to develop human thinking abilities to develop the perfection of human dignity and worth as God's creatures on earth.